Diabetic Neuropathy: One disease or two? - Callaghan, Brian C. (Curr Opin Neurol, 2012)
PURPOSE OF REVIEW: To compare and contrast the evidence for the effect of glucose control on the prevention of neuropathy in type 1 (T1DM) and type 2 (T2DM) diabetes mellitus. RECENT FINDINGS: In T1DM, multiple clinical trials have demonstrated a large benefit from enhanced glucose control, whereas the benefit in T2DM is much more modest. Epidemiologic and laboratory evidence exists to support factors other than hyperglycemia in the development of neuropathy including obesity, hypertension, dyslipidemia, inflammation, and insulin resistance. SUMMARY: T1DM neuropathy and T2DM neuropathy are fundamentally different. In T1DM, glucose control has a large effect on the prevention of neuropathy; therefore future efforts should continue to concentrate on this avenue of treatment. In contrast, in T2DM, glucose control has a small effect on the prevention of neuropathy; as a result, more research is needed to define the underlying mechanisms for the development of neuropathy. Understanding these mechanisms may lead to novel therapeutic approaches to prevent or treat diabetic neuropathy.